Pharmacogenomics: emphasis on clinical drug development - Warner, Amelia (Henry Stewart Talks, 2012)
The promise of genomics, The complexity in predicting therapy, Pharmacogenomic data impact & implementation barriers, Opportunity of personalized medicine, Costs of genomic technologies and the research & development 'process', Scientific challenges for pharma R&D and primary barriers to successful genetic research, Reasons for research failures, Getting the right medicine to the right patients, Translational collaborations in drug discovery, Future biomedical research and vision while keeping privacy protection and value proposition in mind